PENINGKATAN KEMAMPUAN MOTORIK KASAR MELALUI PERMAINAN TRADISIONAL ENGKLEK PADA ANAK USIA 4-5 TAHUN - Umu Choiro; Murjiati .; Nur Aini Zaida . (Universitas Al-Hikmah Indonesia, 2021)
This study aims to explain the improvement of the gross motor skills of group A children RA Darul Ilmi Tegalsari through the traditional crank game. This type of research is classroom action research. The subjects of this study were 13 children of group A RA Darul Ilmi Tegalsari consisting of 8 boys and 5 girls. The data collection method is done through observation and documentation. The data analysis technique was carried out in a descriptive qualitative manner. Increasing gross motor skills is said to be successful if at least 75% of the number of children reaches the criteria for developing as expected. Based on the results of the research and discussion, it can be concluded that gross motor skills can be improved through the traditional game of crank by throwing the gacuk into the first plot, then the children jumping over plots 1, 2, 3, 6 and 9 using one leg and plots number 4, 8. , and 9 to jump on two legs. The increase in gross motor skills of children can be shown from the data on gross motor skills in the initial condition of the child who completed 23.84% or 3 children, in the first cycle of meeting I the children who completed it increased to 38.46 or 5 children, in the first cycle of the second meeting of children who complete increased to 53.85% or 7 children. In the second cycle of the first meeting of the children who completed it increased to 69.23% or 9 children and in the second cycle of the second meeting, the children who completed increased to a maximum of 92.30% or 12 children.